The Effect of Sound Design on the Serious Game Venci's Adventures Experiences - ZiJing Cao (2022)
Abstract Sound design is an essential part of serious game design. The present thesis aims to investigate the sound design effects on people's experiences in serious games. First, based on the selected series game "Venci's Adventures", three different versions of the game were produced: the serious game with standard sounds (the standard sound version), the serious game without sound (the no-sound version), the serious game with an additional auditory notification besides the normal sounds (the notification version). By using these three versions of games, two experimental conditions and the corresponding questionnaires were designed. In total, 23 participants were arranged to join these two experiments randomly. After all, participants played different versions of the serious game during the experiment. They were asked to finish the corresponding questionnaires to record their experiences. In the end, the results from the questionnaires were analyzed in detail by using the method called Analysis of Variance (ANOVA). Three main conclusions were obtained: 1. Compared to the no-sound version of the serious game, adding standard sound to the serious game has positive effects on participants' overall perceived experiences, including competence, flow, and immersion. Meantime, it also decreases participants' negative experiences in the aspect of tension and challenge. 2. Compared to the standard sound version of the serious, inserting well-designed notification sound in the important episodes of the game has a significant positive effect on strengthening users' perceived attention. 3. The present thesis proves that the specific types of sound, Earcons, created by using musical notes to represent auditory notifications, are able used to improve the user's attention in a serious game.